Results of isolated limb perfusion for metastasized malignant melanoma. (September 2021) - Schellerer, Vera S.; Frenger, Johannes; Merkel, Susanne; Goehl, Jonas; Kersting, Stephan; Gruetzmann, Robert; Erdmann, Michael; Foertsch, Thomas
Abstract: Background and objectives: Locoregional metastases are typical biological manifestations of advanced malignant melanomas. Treatment with hyperthermic isolated limb perfusion (HILP) should be considered in affected patients. In the present study, we have analyzed the results of HILPs performed in our department. Patients and methods: Eighty patients with locoregional metastases of the extremities received HILP at the Department of Surgery between January 2007 and December 2016. The mean follow-up was 38 months. Results: The study included 50 men and 30 women (mean age: 63 years). The median time between melanoma diagnosis and HILP was 25 months (range: 1–219 months). HILP was performed in curative (n = 45) and palliative (n = 35) intention. Seventy-five patients received a drug combination of melphalan/dactinomycin and five patients received a drug combination of melphalan/tumor necrosis factor-alpha. Remission rates were determined in 72 of 80 patients (90%) as follows: partial response n = 28, complete response n = 25, no response n = 19. Of the 25 patients with complete response, 13 patients developed a new tumor manifestation during follow-up (locoregional recurrences n = 4; distant metastases n = 3; both n = 6). The median overall survival rate was 33 months. Tumor stage influenced the survival rate significantly (p = 0.001). Patients with complete response showed a significantly better overall survival than patients with partial or no response (p = 0.016). Conclusion: HILP is an effective therapeutic option in patients with locoregional metastases. This procedure carries a certain risk of side effects and adverse events but overall results in good response rates. Therefore, HILP should be offered to selected patients based on an individual discussion, considering their health status and oncological prognosis. Highlights: HILP is an effective therapeutic option for locoregional metastases of melanoma. HILP should be offered to selected patients considering their health status. Complete response to a HILP leads to significantly better survival.